TARGET Approach Through Virtual Bulletin To Increase Early Adult Achievement Motivation - Hajar, Siti; Widiastuti, Haning Tri (EPIK: Edukasi Penerapan Ilmu Konseling, 2022)
The industrial era 4.1 brought the will of technology and information that made almost all lines of life required to be able to adapt to changes. The adaptation required has also penetrated the world of education, the delivery of information that occurs between lecturers and students has now changed. In the past, the delivery of information only took place face-to-face, now it has varied. Various methods and media that can be chosen must be able to take advantage of technological advances as assistance in fostering student competence. This condition gives rise to the view that it is important to equip students with various knowledge and opportunities to be able to take advantage of various technologies and ease in accessing information. Virtual bulletins as a form of channeling student expression in the digital world according to their potential. The direction of the virtual bulletin with the TARGET approach (Tasks, Authority, Recognition, Grouping, Evaluation, Time / Ames 1992) to increase student achievement motivation in accordance with their potential as well as have a positive impact on their future career maturity. The strategy in the TARGET approach in the preparation of Virtual Bulletins with the target of early adulthood (FKIP UHAMKA BK students). Action Research is designed to increase student achievement motivation according to their potential.